Economic risk in the production of Angus and Hereford beef in La Posta, Chihuahua, Mexico - Callejas-Juárez, Nicolás (2020)
Introduction. Risk preference is the situation in which an agricultural producer decides to invest money and there is a probability of obtaining benefits from those desired. Objective. To evaluate risk preference and utility of intensive Angus and Hereford beef production in Rancho Teseachic, La Posta, Chihuahua, Mexico through monetary utility. Materials and methods. The experiment was conducted from March 24th to August 11th 2017. 52 cattle were evaluated and fed for a period of 141 days with rolled corn (53,3 %) and distillers’ grain (37,8 %). The animals were divided into two lots: one with 32 Angus heads with 226.28±28.69 kg of initial live weight and the other with 20 Hereford heads with 191.58±24.23 kg of initial live weight. An econometric model was adjusted, using Ordinary Minimums Squares, to determine the absolute and relative risk preference of the monetary utility in cattle fattening. Results. At the end of the period, the weight was 371.7±43.96 kg for Angus and 320.9±37.99 for Hereford. The production model indicated an optimum live weight at slaughter of 375.5 kg for Angus and 321.5 kg for Hereford. Conclusion. The producer rejected the risk-free preference to the risky preference. Meat production with Angus calves showed a lower risk preference (20 %) than Hereford calves (44 %) and therefore less utility.